Human Immunodeficiency Virus Status Does Not Independently Predict 2-Year Complications Following Total Knee Arthroplasty - Elzomor, Amir; Malyavko, Alisa; Agarwal, Amil R.; Cohen, Jordan S.; Campbell, Joshua; Golladay, Gregory J.; Thakkar, Savyasachi C. (The Journal of Knee Surgery, 2022)
With improved treatment for human immunodeficiency virus (HIV), the demand for total knee arthroplasty (TKA) in this population has increased. Studying the relationship between HIV and postoperative complications following TKA will allow orthopaedic surgeons to accurately assess their patients' surgical risk and provide appropriate counseling. This study aims to understand how HIV impacts surgical and medical complications following TKA for osteoarthritis (OA). Patients identified in a national insurance database who underwent TKA for OA from 2010 to 2019 were divided into three cohorts: no HIV, asymptomatic HIV, and acquired immunodeficiency syndrome (AIDS). Univariate and multivariable regression analyses were performed to determine 90-day postoperative complications as well as 2-year surgical complications (revision surgery, prosthetic joint infection, aseptic loosening, and manipulation under anesthesia). A total of 855,373 patients were included, of whom 1,338 had asymptomatic HIV and 268 had AIDS. After multivariable regression analysis, patients with HIV had no difference in 2-year surgical complications relative to the control cohort. Within 90 days postoperatively, patients with asymptomatic HIV had increased odds of arrhythmia without atrial fibrillation and lower odds of anemia. Patients with AIDS had increased odds of anemia and renal failure. Patients with HIV and AIDS are at an increased risk for developing 90-day medical complications and 2-year surgical complications. However, after accounting for their comorbidities, the risk of 90-day complications was only mildly increased and the risk of 2-year surgical complications approximated the control cohort. Surgeons should pay particular attention to these patients' overall comorbidities, which appear to be more closely associated with postoperative risks than HIV status alone. Level of evidence: III.
Keywords: total knee arthroplasty; human immunodeficiency virus; acquired immunodeficiency syndrome; postoperative complications; medical complications; surgical complications